Member - Georgiou, Yiannis (My University, 2026)
Contributing to the development of editorial and publications policies, processing copyright requests, providing assistance to the conference organizers each year regarding publication of conference proceedings, and enhancing the visibility and accessibility of the ISLS conference proceedings and journal publications.